(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The origin of human nature and the right of man to rest. A biblical perspective on the concept of rest. In this study, we aim to investigate the relationship between the origin of human nature and the human rights. This discussion will be customized to the right of man to rest. Therefore, we want to outline a theology of rest based on the development of the concept of rest throughout the Bible, in order to establish its importance for discussions about the human right to rest. Given this analytical approach, we intend to show first that rest was implanted in the natural rhythm of life by God, who rested on the seventh day of creation, was regulated in The Dacalogue and then is promised as heavenly rest. The whole Bible evokes a picture of the extreme importance of rest time. Thus rest presents the time of doing good, in order to develop relationships with peers, behavior and physical recovery, interruption and limit of physical work and maintaining a close relationship between man and God by manifesting trust in His providence, worship, gratitude and observance of the prescriptions of the Law.